Crazy rich Asians [videorecording (DVD)] - Chu, Jon M. (Jon Murray), 1979-; Wu, Constance, 1982-; Golding, Henry, 1987-; Yeoh, Michelle, 1963-; Kwan, Kevin (Warner Bros. Entertainment, 2018)
When an American-born Chinese woman attends a wedding in Singapore with her boyfriend, she discovers that his family is very wealthy and other women in his social class are trying to date him.